1999
DOI: 10.1677/joe.0.1630007
|View full text |Cite
|
Sign up to set email alerts
|

The different approaches to the genetic analysis of autoimmune thyroid disease

Abstract: Graves' disease and Hashimoto's thyroiditis are organspecific autoimmune disorders of multifactorial aetiology with a polygenic mode of inheritance. Familial clustering and twin studies provide evidence for a genetic predisposition. Three main approaches have been used in the search for susceptibility loci: population-based case-control studies, classical linkage analysis, and intrafamilial linkage disequilibrium. Case-control studies are a sensitive method of gene detection and the collection of subjects is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…For example, the ratios of mother-children to father-children and parents-daughter to parents-son were 3.0 (180/60) and 4.6 (83/18), respectively, which were similar to the female/male ratio of the whole GD family, 3.2 (360/114). It is well recognized that both GD and HT are frequently found in members of the same family, implying a shared genetic predisposition [19,20]. In the present study, approximately 8% of familial GD patients had HT in their first-degree relatives, supporting the existence of shared genes.…”
Section: Discussionsupporting
confidence: 76%
“…For example, the ratios of mother-children to father-children and parents-daughter to parents-son were 3.0 (180/60) and 4.6 (83/18), respectively, which were similar to the female/male ratio of the whole GD family, 3.2 (360/114). It is well recognized that both GD and HT are frequently found in members of the same family, implying a shared genetic predisposition [19,20]. In the present study, approximately 8% of familial GD patients had HT in their first-degree relatives, supporting the existence of shared genes.…”
Section: Discussionsupporting
confidence: 76%
“…One study in particular that targeted the HLA region found no association with autism [36]. However, genome sib-pair linkage studies also have not detected HLA involvement in several autoimmune diseases such as multiple sclerosis, systemic lupus erythematosus, Graves' disease, and Hashimoto's thyroiditis, contrasted with other methods of genetic analysis that laid the groundwork for HLA-autoimmune associations [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Although this report examined a variable (AT) n repeat sequence in the 39 untranslated region in exon 4 subsequent studies have focused more on the A-G repeat because, as an SNP, it is more suitable for case control study analysis (20) and it is in linkage disequilibrium with the (AT) n . Subsequent to the first report of an association with Graves' disease a number of investigators have reported association of the CTLA-4 gene with a variety of autoimmune disorders suggesting that the CTLA-4 gene region is acting as a susceptibility locus for the autoimmune disease process in general (21).…”
Section: Discussionmentioning
confidence: 99%